Nulla executio sine titulo: el escrutinio de los laudos en la práctica del arbitraje internacional como mecanismo para optimizar la ejecución de los laudos en el Perú - Rivarola Reisz, José Domingo (2017)
What is «liquidable» and how should this concept be faced by arbitrators and judges? Can an enforcement judge determine concepts such as costs, interests and/or penalties if the arbitral tribunal has not provided any parameters? What fundamental rights might be violated? In accordance with international arbitration practice, we will deal here with the problems arising from the division of functions between judges and arbitrators in relation to the enforcement of the «liquidable» concepts.